Mammals’ abundance in Lingga Isaq Hunting Park Landscape, Aceh - CUT MAILA HANUM; MA’RIFATIN ZAHRAH; MALAHAYATI DAUD; ROZZA TRI KWATRINA (Universitas Syiah Kuala, 2022)
Hunting-park is a conservation area with the unique attraction of periodically hunting in terms of wildlife management. Lingga Isaq Hunting-Park (LIHP) is one of 13 hunting parks in Indonesia. However, the utilization of LIHP as a hunting park is still facing obstacles; two of which are conflicts of interest among authorities and no data of the animals, especially mammals – the most hunted creatures in the park. Therefore, a study was conducted to identify the mammalian abundance and distribution. This data would be usefull as essential decision-making for hunting-tourist attractions in LIHP. This study used the transect method, with 12 transect strips evenly distributed in those four function areas; three per each. We found 11 species of mammalian that belonging to 8 families. The protected forest had the highest biodiversity value (H’=1.50), while other use areas had the lowest biodiversity value (H’=1.16). Macaca fascicularis had the highest abundance (23 individu), while Sus scrofa was the most evenly distributed mammal in the whole landscape. Protected forests and other utilization areas have the highest habitat similarity, identified as having intense anthropogenic activities. The protected forest also has habitat similarity with hunting-park as both areas are legally protected. Nevertheless, there are only Cervus unicolor, Muntiacus muntjak, and Sus scrofa that are highly recommended for hunting tourism attractions.